IMPLEMENTATION OF ARTICLE 9 OF THE REPUBLIC OF INDONESIA GENERAL ELECTION COMMISSION REGULATION NUMBER 14 OF 2015 BY THE GENERAL ELECTION COMMISSION OF PASAMAN REGENCY - Alberd Alberd; Nur Asmah (Ikatan Dosen Menulis, 2024)
Regional head elections are a democratic agenda that is carried out directly as mandated by the 1945 Constitution of the Republic of Indonesia. Based on the Election Vulnerability Index of the Indonesian Election Supervisory Agency (Bawaslu RI), West Sumatra Province is classified as a vulnerable area, with Pasaman Regency as the only regency holding the 2020 Pilkada with a single candidate pair. This condition raises the issue of equal treatment between single candidate pairs and blank columns in the implementation of the campaign. This study aims to analyze the implementation of Article 9 of the Indonesian General Elections Commission Regulation Number 14 of 2015 by the Pasaman Regency KPU and identify obstacles to its implementation. The research method used is empirical juridical with qualitative analysis. The results of the study indicate that the Pasaman Regency KPU has implemented the provisions of Article 9 of the Indonesian General Elections Commission Regulation Number 14 of 2015 in the 2020 Simultaneous Pilkada. However, its implementation faces various obstacles, including the lack of legal regulations regarding the position of blank column volunteers, campaign techniques, campaign props, campaign funding, as well as the regulation of witnesses and vote count recapitulation for blank columns.